Особливості розвитку лікувально-оздоровчого туризму в регіонах України - Мельник, Людмила Вікторівна; Батиченко, Світлана Павлівна (My University, 2018)
Розкрито теоретичні питання лікувально-оздоровчого туризму. Проаналізовано стан та розвиток санаторно-курортної бази, яка є основою лікувально-оздоровчого туризму. Висвітлено питання попиту серед населення на послуги лікувально-оздоровчого туризму. Досліджено питання центрів лікувально-оздоровчого туризму в Україні та в країнах Європи. Проаналізовано динаміку чисельності санаторно-курортних закладів в регіонах України за період з 2011-2017 рр. The theoretical questions of health-improving tourism are revealed. Health-improving tourism is a type of tourism aimed at restoring health or preventing (preventing) diseases. In recent times, the term «wellness» has become popular, which can be defined as observing a healthy lifestyle aimed at harmonious development of the individual. Wellness centers and wellness-hotels are becoming a place of recreation and at the same time a place of social communication. The state and development of the sanatorium-resort base, which is the basis of medical and health tourism, is analyzed. The issue of demand among the population for health and wellness tourism services is covered. The issue of the centers of health-improving tourism in Ukraine and in the countries of Europe has been investigated. The dynamics of the number of sanatorium and spa establishments in the regions of Ukraine for the period from 2011-2017 is analyzed.
Keywords: туризм; лікувально-оздоровчий туризм; санаторно-курортні заклади; регіони України; wellness; spa-курорти; кафедра туристичного та готельного бізнесу; spa-курорты; tourism; health-improving tourism; sanatorium and resort establishments; regions of Ukraine; wellness; spa-resorts